Portrait of WWP1: the current state in human cancer - Lei, Jiaming; Chen, Jun; Yu, Wenwen; Wu, Qing; Jing, Shuang; Tang, Yuanguang; Lin, Li; Hu, Meichun (Frontiers in Cell and Developmental Biology, 2025)
WWP1, a member of the C2-WW-HECT E3 ligase family, is an E3 ubiquitin-protein ligase containing WW domains. This enzyme plays a critical role in regulating diverse cellular processes. Its expression is modulated by various factors and non-coding RNAs, resulting in ubiquitination that affects substrate protein degradation. WWP1 demonstrates a dual function, acting predominantly as an oncogene in tumors but occasionally as a tumor suppressor. This review summarizes WWP1’s biological roles, therapeutic potential in oncology, upstream regulatory factors, and downstream substrates. It aims to promote research on WWP1’s antitumor effects, improve understanding of its role in tumorigenesis, and support the development of targeted therapies.